The Impact of Accessible Email on the Written Communication of People with Aphasia - (:unkn) unknown (My University, 2014)
Aphasia is a language disorder affecting individuals' ability to speak, listen, read, and write. Because of repeated communication breakdowns, people with aphasia often avoid social interactions, which can lead to feelings of social isolation. Email may reduce the frustrations of face-to-face communication by providing additional time to compose and revise messages. The purpose of this study was to investigate how the use of email would impact functional communication and social participation in people with aphasia. A single-subject, multiple-baseline across participants design was used to evaluate the effect of a simplified email program on participants' written communication skills and feelings of social isolation. Two individuals with moderate aphasia participated in the study; a 52-year-old female, two years post-onset and a 72-year-old female, three years post-onset. Participants were instructed how to use a simplified email program until the program was mastered. Composition time and error rates were analyzed to determine if there was any change in written communication skills. Both participants saw a decrease in composition rates, while error rates for both participants were unchanged. Effective conveyance of intended messages were judged by unfamiliar readers using a 5-point rating scale. One participant reported an increase in her comprehension abilities, while comprehension ratings of the other participant decreased over the course of the study. Feelings of social isolation and satisfaction with the instructional program were evaluated using surveys. While both participants were satisfied with the CogLink program, neither participant experienced a measurable change in feelings of social isolation.
Keywords: Aphasia; Assistive Technology; Email